Contemporary theater and voice: the context of vocal preparation in Samuel Beckett's short plays (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article intends to point out some of the aspects that were established in the theatrical scene from the transformations and revolutions after the end of the 19th century, a period in which it was possible to observe the interweaving between plastic arts, music, dance, cinema, video and performance, providing opportunities for an aesthetic plurality that overflows and exceeds the dramatic text. Such experiments stimulated new ways of understanding how the voice emancipated itself from a compilation of signs linked to the dramatic text, reverberating in new ways of activating the practices and poetics that touch the voice. From this panorama, reports of vocal practices in the montage of some short pieces by the Irish author Samuel Beckett, developed with interpreters from Brasilia, will be presented.
Keywords: Contemporary Theater; Voice; Vocal Preparation